Bullous pemphigoid and epidermolysis bullosa acquisita: presentation, prognosis, and immunopathology in 11 children. - Edwards, S; Wakelin, S; Wojnarowska, F; Marsden, R; Kirtschig, G; Bhogal, B; Black, M (1998)
The immunobullous diseases bullous pemphigoid (BP) and epidermolysis bullosa acquisita (EBA) are very rare in childhood. Although case studies have been detailed, there are no reports of a large series of patients documenting the effectiveness of treatment and long-term prognosis. We report the clinical presentation, immunopathologic features, disease course, and long-term prognosis of BP and EBA in a series of 11 children. The initial diagnoses based on clinical features were BP (5), EBA (3), and chronic bullous disease of childhood (CBDC) (3). These were subsequently revised from BP to EBA (2), CBDC to BP (2), and CBDC to BP or EBA (1) following the results of direct and indirect immunofluorescence and immunoblotting. Analysis of IgG subclasses in eight cases showed that the predominant subclasses were IgG1 (8) and IgG4 (6). The clinical features appeared to be highly variable, and in patients presenting with inflammatory blistering, laboratory studies were required in order to differentiate between BP and EBA. All patients improved on treatment with corticosteroids and/or sulfones, although treatment regimens showed wide variation. Their diseases tended to remit within 2 years, and their long-term prognosis was good.